Application of Project Based Learning with the Role Playing Method in Overcoming Students' Learning Difficulties in One Variable Linear Equations - Astri, Agustina Rina; Bawani, Asri; Cipta, Dyah Ayu Sulistyaning (Cakrawala, 2023)
Mathematics learning at junior high school level is often faced with the challenge of conceptual complexity, especially in the topic of linear equations in one variable. This article discusses classroom action research which aims to overcome the learning difficulties of class VII students at Cor Jesu Catholic Middle School, Malang, in solving linear equations with one variable, especially in the context of word problems. By applying the Project-Based Learning (PJBL) learning model with the Role playing method, this article provides an overview of the experience of implementing this strategy and the results obtained. The research method used is a qualitative approach with descriptive methods. The learning outcomes using the project-based learning model with the role playing method are very satisfying. Students not only managed to solve the questions better, but they were also able to explain concepts more clearly through role playing. The research results showed that students not only succeeded in solving questions better but were also able to explain concepts more clearly through role playing. This learning process increases motivation and strengthens understanding of the concept of linear equations in one variable as a whole. This approach makes mathematics learning more interesting and relevant to students' daily lives.